"Propuesta de mejora de las contrataciones orientándola a la gestión por resultados en el proyecto especial Chavimochic 2015-2016" - Alayo Castañeda, James Segundo (2017)
ABSTRACT CHAVIMOCHIC is one of the biggest and important projects in the Peru. This project, culminated in its first stage in 1992, contributes to the development of our Country and of the Region La Libertad. Being model of a modern agriculture, generating important employment levels and economic and social development in the Region. The purchase and recruiting processes are vital in all Entity since they assure the supply of resources and services for the normal development of their diverse activities, but the obtaining of these products and services should be carried out according to the normative one in benefit of the Institution, the city and the supplying companies, The present investigation is guided to achieve efficiency and effectiveness in the recruiting processes summoned by the Special Project CHAVIMOCHIC. The work of made field, as well as the analysis of the documentation, allowed to outline the application of an appropriate training, coordination and modelation with the purpose of carrying out recruiting processes that you/they allow to fulfill the annual Goals of the PECH whose starting point is the Annual Plan of Recruitings (APR). For it was necessary to apply the descriptive method; that it´s worked with an aleatory sample of 20 people between officials and employees; to who were applied a questionnaire and focus group to gather information, the results were taken to statistical squares, finally the conclusion achieved that applying the Law of Recruitings of the State appropriately and their regulation will be achieved effectiveness in the Recruitings.